CPT314 - Automata Theory & Formal Languages - March 2005 - PPSKOM, Pusat Pengajian Sains Komputer (2005)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 2004/2005 March 2005 CPT314 - Automata Theory & Formal Languages Duration : 3 hours